Analisis Kelayakan Usahatani Timun Apel (Studi Kasus : di Desa Tanjung Pakis, Kecamatan Pakis Jaya, Kabupaten Karawang) - Rahmawaty Irwan Darise; Abubakar Abubakar; Luthfi Nur’azkiya (Peneliti.net, 2021)
This study aims are : (1) to determine the cost, receipt, revenues and profits obtained in apple cucumber farming in Tanjung Pakis Village, Pakis Jaya District, Karawang Regency and (2) To know the feasibility of apple cucumber farming based on R/C and BEP. The results showed that the average total cost of apple cucumber farming in Tanjung Pakis Village, Pakis Jaya District, Karawang Regency was Rp.8.086.344/season, The average revenue earned was Rp.25.217.000/season, so the average revenue was Rp.17.893.650/season while the average profit was Rp.17.130.656/season with an average land area of 0,9375 Ha. Apple cucumber farming is seen from R/C this effort is feasible because the value of R/C is greater than one, namely 3,1184 and to reach the break even point minimum must sell apple cucumbers as much as 150,16 Kg for Super and 8,02 Kg for PL with a selling price of Rp.2.179,60/Kg and produce BEP Revenue of Rp.1.075.265,23. So it can be concluded that apple cucumber farming is worth trying based on financial aspects and this business is profitable.